Ethanol Extract of Gotu Leaves (Centella asiatica (L.) Urban) Increases PDGF Levels but Does Not Change TNF-α and Malondialdehyde in Wistar Rats in a Carrageenin-Induced Acute Inflammatory Model - Mira Mustika; Endy Juli Anto; Jekson Martiar Siahaan (GLOBAL HEALTH SCIENCE GROUP, 2026)
Conventional anti-inflammatory therapies with NSAIDs and glucocorticoids are limited by gastrointestinal, renal, and metabolic side effects, thus encouraging the search for plant-based alternatives. Gotu kola leaves (Centella asiatica (L.) Urban) are rich in triterpenoids and flavonoids which are reported to have anti-inflammatory and wound-healing activities. This study aimed to analyze the effect of gotu kola leaf ethanol extract on tumor necrosis factor-alpha (TNF-α), platelet-derived growth factor (PDGF), malondialdehyde (MDA), and leg edema volume in male Wistar rats with carrageenan-induced acute inflammation model. Thirty rats were randomized into five groups (n=6): normal, negative control (carrageenan), positive control (carrageenan + sodium diclofenac), and two extract treatment groups of 2 g/kgBB and 4 g/kgBB orally. Edema was measured with a plethysmometer in the first minute and every hour for 4 hours; Serum TNF-α, PDGF, and MDA levels were measured by ELISA. Data were analyzed with one-way ANOVA and LSD follow-up test (α=0.05). Screening for positive phytochemicals of flavonoids, alkaloids, saponins, tannins, phenols, glycosides, and steroids/triterpenoids. PDGF levels differed significantly between groups (p=0.001), highest in the 4 g/kgBB group (2.14±0.12 ng/mL) and lowest in the negative control (1.66±0.10 ng/mL). The volume of edema was significantly different at the beginning and 1st hour (p=0.001) but not at the 2nd to 4th hour. The levels of TNF-α (p=0.423) and MDA (p=0.072) were not significantly different. Ethanol extract of Centella asiatica leaves, especially at a dose of 4 g/kgBB, increased PDGF and decreased early-phase edema, showing modulation potential towards tissue repair, but had no significant effect on TNF-α and MDA in this acute model.